2018
DOI: 10.1515/geo-2018-0069
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Structure around Mt. Pandan, Madiun, East Java, Indonesia and Its Relationship to 2016 Seismic Activity

Abstract: Java Island is part of the island arc influenced by subducting Indo-Australian beneath Eurasian tectonic plates, therefore there is high seismic activity and an active volcanic chain trending East-West. One of the volcanoes in Java Island is Mt. Pandan, northern part of Madiun, East Java region, which is known as one of the dormant volcano in the region. According to the list of volcanoes in Indonesia Mt. Pandan is not classified as an active volcano. The previous studies mentioned that Mt. Pandan is a modern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This area is about 40 km northeast of Madiun city. Smyth et al have defined mount Pandan as a modern volcanic center [4], which is confirmed by Santoso et al in the previous study [5]. The subsurface conditions in this area are interesting to investigate because they have a tectonic and magmatic activity that might be correlated with the magma source.…”
Section: Case Studysupporting
confidence: 68%
“…This area is about 40 km northeast of Madiun city. Smyth et al have defined mount Pandan as a modern volcanic center [4], which is confirmed by Santoso et al in the previous study [5]. The subsurface conditions in this area are interesting to investigate because they have a tectonic and magmatic activity that might be correlated with the magma source.…”
Section: Case Studysupporting
confidence: 68%
“…Further to the north, a low density anomaly was observed beneath Mt. Pandan (Santoso et al 2018), suggested as the presence of hot material because of the hot springs and warm ground. Small earthquakes were observed (M < 4), which are concentrated beneath Mt.…”
Section: Discussionmentioning
confidence: 99%
“…Pandan at the depth of less than 10 km dipping to the southward. Santoso et al (2018) suggested that the small earthquakes, which occurred in 2016, may lead to the Kendeng fault activity located northward of Mt. Pandan.…”
Section: Discussionmentioning
confidence: 99%
“…Pandan (Santoso et al 2018), Jailolo volcano (Nugraha et al 2018a), Bekancan (Nugraha et al 2018b), the southern part of Garut, West Java (Supendi et al 2018), West Halmahera (Nugraha et al 2017b) among many others. Albino et al (2019) suggested that the dike intrusion between neighboring arc volcanoes was responsible for the Mt.…”
Section: Open Accessmentioning
confidence: 99%